Methodical instructions for independent work on the discipline "First emergency premedical aid in emergency situations" - Tverdokhliebova, Natalia Evgeniivna (Національний технічний університет "Харківський політехнічний інститут", 2024)
This methodological development involves students performing educational tasks in accordance with the individual curriculum in the discipline “First Emergency Medical Care in Emergency Situations", which corresponds to the final specific learning outcomes.
Keywords: emergency situations; first premedical aid; injuries; methodical instructions; independent work